2018
DOI: 10.18844/cjes.v13i2.2938
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Patterns for Smartphone Addiction: Age, Sleep Duration, Social Network Use and Fear of Missing Out

Abstract: The aim of this study is to examine high school students and uncover the relationships between Smartphone Addiction levels and certain factors such as (a) Fear of Missing Out (FoMO) (b) Social Networking Site (SNS) usage habits (using smartphones), (c) age, d) sleep duration and (e) duration of smartphone ownership. The study group consists of 161 students from two public high schools in Turkey. Two different scales were employed for data collection; namely, the Smartphone Addiction Scale and FoMO Scale. Based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
41
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 50 publications
7
41
1
7
Order By: Relevance
“…The importance attributed to using the device for work purposes was not statistically correlated to smartphone use scores. Others have previously reported a connection between smartphones use and use of social networks (Haug et al, 2015;Arnavut et al, 2018;Gezgin, 2018;Sha et al, 2019). However, we did not find any previous studies on the importance attributed to specific social apps.…”
Section: Predictorcontrasting
confidence: 93%
See 3 more Smart Citations
“…The importance attributed to using the device for work purposes was not statistically correlated to smartphone use scores. Others have previously reported a connection between smartphones use and use of social networks (Haug et al, 2015;Arnavut et al, 2018;Gezgin, 2018;Sha et al, 2019). However, we did not find any previous studies on the importance attributed to specific social apps.…”
Section: Predictorcontrasting
confidence: 93%
“…6. More use of different social network apps was related with higher smartphone usage (Arnavut et al, 2018;Gezgin, 2018;Haug et al, 2015;Kircaburun & Griffiths, 2018). 7.…”
Section: No Relation Would Be Found Between Familymentioning
confidence: 98%
See 2 more Smart Citations
“…State-FoMO has been found to directly and indirectly impact phubbing via problematic Instagram use, whereas trait-FoMO has been indirectly associated with phubbing via state-FoMO and problematic Instagram use (24). Additionally, some studies have shown the associations between high levels of FoMO and negative outcomes, such as bad school performance, fatigue, and decreased sleep (25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%